(3QSGdI TQM deYI ef CNHGQ GdEeGe GdeYR dOjf Gddgs - (3eLghds
(3ChdgG (B:s
(3TQM deYI ef CNHGQ GdEeGe GdeYR dOjf Gddg hJSjjQg YSGcQg Edi eUQ hMVhQg EPG cGf QGaY YedgG gPg fSHJge GdJi jfJSHhf EdjgG hGdfSGHhf jfcQhf Pdc dGSjeG Cgd HZOGO s
(3BNQgG (B:s
(3adeG edc CHQgI edc GdMHTI GHfg HcShe adeG Jedc HcShe edc ef HYOg CNhg eTQhb Hf CHQgI GfJgi edNUfG ef SjQI Hf ESMb Yf Hf gTGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbHjIs
(3YdjgG Jedc SfI (B920(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs